Inadequate and Late Antenatal Contacts Among Saudi Mothers: A Hospital-Based Cross-Sectional Study - Al-Wutayd O (Dove Medical Press, 2020)
Osama Al-Wutayd Department of Family and Community Medicine, Unaizah College of Medicine and Medical Sciences, Qassim University, Unaizah, Saudi ArabiaCorrespondence: Osama Al-Wutayd Email Osama.alwutayd@gmail.comBackground: Antenatal care is a major contributor to the reduction of perinatal and maternal mortality and morbidity, through the identification of high risk pregnancies and early intervention for pregnant women with complications. Inadequate (less than eight contacts) and late antenatal care (starting after 12 weeks) have implications for the health of mothers, fetuses, and newborns. The aim of this study was to assess proportion and determinants of inadequate and late antenatal care among Saudi mothers in Unaizah, Qassim, Saudi Arabia.Methods: This was a cross-sectional study among 537 mothers who gave birth at King Saud Hospital, Unaizah City. Face-to-face interviews were conducted using a structured questionnaire covering sociodemographic information, antenatal care, and determinants that might affect the use of antenatal care. The data were entered into Excel and exported in STATA version 16. Simple and multiple logistic regressions were used to identify the determinants of inadequate and late antenatal care.Results: The mean (standard deviation) age of the participants was 30.71 (5.73) years. The proportion of inadequate and late antenatal care was 34% (95% CI 30– 38) and 25% (95% CI 21– 29). Inadequate antenatal care was independently associated with employed mothers (OR 1.91, 95% CI 1.13– 3.22) and high parity (three or more) (OR 2.21, 95% CI 1.17– 4.16). Late antenatal care was independently associated with employed mothers (OR 1.87, 95% CI 1.07– 3.27) and high parity (OR 2.04, 95% CI 1.01– 4.16).Conclusion: This study found that the proportion of inadequate and late ANC was less than in other regions of Saudi Arabia, but it is still important to decrease this rate. The findings of this study will be useful for policy makers in Qassim region to help them design interventions to target mothers at high risk of inadequate and late ANC.Keywords: antenatal care, determinants, Qassim, Saudi Arabia, parity, employment